α-Adrenergic Blockade Unmasks a Greater Compensatory Vasodilation in Hypoperfused Contracting Muscle - Casey, Darren P.; Joyner, Mike (Frontiers in Physiology, 2012)
We previously demonstrated that acute hypoperfusion in exercising human muscle causes an immediate increase in vascular resistance that is followed by a partial restoration (less than 100% recovery) of flow. In the current study we examined the contribution of α-adrenergic vasoconstriction in the initial changes in vascular resistance at the onset of hypoperfusion as well as in the recovery of flow over time. Nine healthy male subjects (29 ± 2) performed rhythmic forearm exercise (20% of maximum) during hypoperfusion evoked by intra-arterial balloon inflation. Each trial included; baseline, exercise prior to inflation, exercise with inflation, and exercise after deflation (3 min each). Forearm blood flow (FBF; ultrasound), local (brachial artery), and systemic arterial pressure (MAP; Finometer) were measured. The trial was repeated during phentolamine infusion (α-adrenergic receptor blockade). Forearm vascular conductance (FVC; ml min−1 100 mmHg−1) and resistance (mmHg ml min−1) was calculated from BF (ml min−1) and local MAP (mmHg). Recovery of FBF and FVC (steady state inflation plus exercise value − nadir)/[steady state exercise (control) value − nadir] with phentolamine was enhanced compared with the respective control (no drug) trial (FBF = 97 ± 5% vs. 81 ± 6%, P < 0.05; FVC = 126 ± 9% vs. 91 ± 5%, P < 0.01). However, the absolute (0.05 ± 0.01 vs. 0.06 ± 0.01 mmHg ml min−1; P = 0.17) and relative (35 ± 5% vs. 31 ± 2%; P = 0.41) increase in vascular resistance at the onset of balloon inflation was not different between the α-adrenergic receptor inhibition and control (no drug) trials. Therefore, our data indicate that α-adrenergic mediated vasoconstriction restricts compensatory vasodilation during forearm exercise with hypoperfusion, but is not responsible for the initial increase in vascular resistance at the onset of hypoperfusion.